Evaluate the applicability of Pont’s index on a sample of Tishreen University - الأحدب سهر; فادي خليل; حازم حسن (Latakia University Journal -Medical Sciences Series, 2024)
Plenty of indices have shown interest about studying the dental arch width and define its features, as Pont’s index. But studies have referred to ethnic differences between peoples, is what made a lot of questions about the applicability of these indices, as Pont’s index, should be asked. Aim: Verify the applicability of Pont’s index as a reliable method for orthodontic diagnosis. Materials and Methods: The research sample included 100 dental cast for patients with permanent normal occlusion. Results: Correlation coefficient values between the measured arch width values and the calculated ones according to Pont’s index were low in all cases. Conclusions: Pont’s index can’t be approved as a reliable method to predict the ideal dental arch width in the study community.